2011
DOI: 10.1007/s00192-011-1401-8
|View full text |Cite|
|
Sign up to set email alerts
|

Differential profile analysis of urinary cytokines in patients with overactive bladder

Abstract: Taken together, the results suggest that a subset of inflammatory cytokines and chemokines provides a framework for development of highly optimized urinary biomarker assay for differential diagnosis and treatment of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 27 publications
2
48
0
3
Order By: Relevance
“…These findings further suggest that a preconditioned state of high inflammation may be present in some patients causing bladder pathology thus contributing to prolonged recovery of continence. Indeed our previous study leading to this investigation postulated that elevated expression of MCP-1 in patients with overactive bladder could contribute to incontinence [10]. Another important aspect of our investigation is the pinning down MCP-1/TV as a potential biomarker to identify subjects that can start medications early in the recovery process.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings further suggest that a preconditioned state of high inflammation may be present in some patients causing bladder pathology thus contributing to prolonged recovery of continence. Indeed our previous study leading to this investigation postulated that elevated expression of MCP-1 in patients with overactive bladder could contribute to incontinence [10]. Another important aspect of our investigation is the pinning down MCP-1/TV as a potential biomarker to identify subjects that can start medications early in the recovery process.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, lack of the knowledge on the preoperative biomarkers alluding to postoperative incontinence is a limiting factor in the counseling process because the information may potentially be used as an additional component at the time of counseling. To this end, a previous study using a proteomics chip based analysis of urinary cytokine expression demonstrated that OAB group expressed Monocyte Chemotactic Protein-1 (MCP-1) two-fold higher than UTI population and controls, thus suggesting MCP-1 to be a potential target for an OAB biomarker [10]. Based on these premises, we conducted a clinical study to assess whether urinary MCP-1 can be a potential preoperative biomarker associated with the outcome of 30-day urinary continence after robotic radical prostatectomy (RRP).…”
Section: Introductionmentioning
confidence: 99%
“…[18], используя люминесцентный ме-тод, выявили значительное увеличение уровней моноцит-хемотаксичного протеина 1-го типа и интерлейкинов (IL-10 и IL-12) у пациентов с ГМП по сравнению с таковыми в контрольной группе. В другом исследовании обнаруже-ны повышение концентрации IL-16 и снижение IL-7 в моче у пациентов с симптомами ГМП [19].…”
Section: мочевые биомаркерыunclassified
“…
Dear Editor, We read with interest the recent paper by Ghoniem et al [1] exploring urinary cytokine profiles of women with overactive bladder (OAB) in comparison to both healthy controls and women with UTI. While we applaud their efforts to apply such innovative techniques, we wish to raise concerns regarding the statistical methods used to analyse data from the cytokine antibody arrays.

The authors report p values <0.05 in association with twofold overexpression for six of the cytokines assayed comparing controls and women with OAB, and for 13 of the cytokines assayed comparing controls and women with UTI.

…”
mentioning
confidence: 99%
“…Dear Editor, We read with interest the recent paper by Ghoniem et al [1] exploring urinary cytokine profiles of women with overactive bladder (OAB) in comparison to both healthy controls and women with UTI. While we applaud their efforts to apply such innovative techniques, we wish to raise concerns regarding the statistical methods used to analyse data from the cytokine antibody arrays.…”
mentioning
confidence: 99%